Pill Esophagitis: Clinical and Endoscopic Profile - Vikas Pemmada; Athish Shetty; Megha Murali; Shiran Shetty; Balaji Musunuri; Siddheesh Rajpurohit; Ganesh Bhat (Journal of Digestive Endoscopy, 2023)
Background Medications can rarely cause esophageal injury and present with acute symptoms. Multiple factors, including the type of medication, comorbidity, and method of ingestion play a role in causing drug-induced or pill esophagitis (PE). We analyzed the clinical, endoscopic, and histopathological profiles of PE cases at our gastroenterology outpatient clinic.